2018
DOI: 10.1111/gcb.14435
|View full text |Cite
|
Sign up to set email alerts
|

Differential use of winter precipitation by upper and lower elevation Douglas fir in the Northern Rockies

Abstract: In temperate regions such as the American west, forest trees often exhibit growth sensitivity to climatic conditions of a particular season. For example, annual tree ring growth increments may correlate well with winter precipitation, but not with summer rainfall, suggesting that trees rely more on winter snow than summer rain. Because both the timing and character of seasonal western climate patterns are expected to change considerably over coming decades, variation in the importance of different seasonal moi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 73 publications
3
33
0
Order By: Relevance
“…Furthermore, the variability in tropical precipitation isotope ratios we show here may be the result of different storm sources and cloud types (Bailey et al, 2017;Scholl et al, 2009). Thus, precisely predicting precipitation isotope cycles at low latitudes without calibration data may (especially) require consideration of circulation patterns and their temporal variability (Cai et al, 2018;Martin et al, 2018b); an alternative option would be using regional multiple regression equations, which performed well in those regions (Fig. 6).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Furthermore, the variability in tropical precipitation isotope ratios we show here may be the result of different storm sources and cloud types (Bailey et al, 2017;Scholl et al, 2009). Thus, precisely predicting precipitation isotope cycles at low latitudes without calibration data may (especially) require consideration of circulation patterns and their temporal variability (Cai et al, 2018;Martin et al, 2018b); an alternative option would be using regional multiple regression equations, which performed well in those regions (Fig. 6).…”
Section: Discussionmentioning
confidence: 92%
“…Quantifying seasonal precipitation isotope cycles also facilitates identification of the proportion (and over-or underrepresentation) of precipitation from different seasons in samples such as surface waters (Bowen et al, 2019;DeWalle et al, 1997;Halder et al, 2015), groundwa-ter (Jasechko et al, 2014;Kalin and Long, 1994;Lee and Kim, 2007), or plant and soil water (Allen et al, 2019). Similarly, ecological and physiological inferences can be drawn by observing how seasonal variations in water isotope signals are incorporated into (or propagate through) plant and animal tissues (Csank et al, 2016;Gessler et al, 2014;Martin et al, 2018a;Vander Zanden et al, 2015;Yang et al, 2016). Even where phase values are poorly constrained, amplitude and offset values are still useful identifiers of typical mean values and magnitudes of seasonal variation.…”
Section: Discussionmentioning
confidence: 99%
“…There are limited data to test how these dynamics might evolve over longer timescales in response to stressors such as decreases in spring snowpack or rising evaporative demand (Mote et al, 2018;Restaino et al, 2016). For example, existing data on water use by conifers in the western United States have indicated that snowmelt, the predominant source of regional recharge, is the primary reservoir to support forest water demand (Bowling et al, 2017;Hu et al, 2010;Marshall & Monserud, 2006;Martin et al, 2018;Phillips & Ehleringer, 1995). However, the snapshots provided by these studies do not indicate how reliance on this water source has varied in response to region-wide changes in the snowpack or lengthening of the growing season.…”
Section: Introductionmentioning
confidence: 99%
“…The use of the stable isotope ratios of hydrogen and oxygen (δ 2 H and δ 18 O values) as a tracer of plant water uptake is increasing rapidly . Investigations of ecohydrological processes using such techniques have improved our understanding of soil water dynamics and patterns of plant water use .…”
Section: Introductionmentioning
confidence: 99%